EMAP: Expedite Message Authentication Protocol for Transport Unexpected Networks - Srinivas, A.; Babu, Stalin (IJRDO -Journal of Computer Science Engineering, 2015)
Vehicular ad hoc networks (VANETs) adopt the general public Key Infrastructure (PKI) and Certificate Revocation Lists (CRLs) for his or her security. In any PKI system, the authentication of a received message is performed by checking if the certificate of the sender is enclosed within the current CRL, and substantiating the genuineness of the certificate and signature of the sender. during this paper, we have a tendency to propose associate degree Expedite Message Authentication Protocol (EMAP) for VANETs, that replaces the long CRL checking method by associate degree economical revocation checking method. The revocation check method in EMAP uses a keyed Hash Message Authentication Code HMACÞ, wherever the key employed in scheming the HMAC is shared solely between non revoked On-Board Units (OBUs). additionally, EMAP uses a completely unique probabilistic key distribution, that permits non revoked OBUs to firmly share and update a secret key. EMAP will considerably decrease the message ratio owing to the message verification delay compared with the standard authentication ways using CRL. By conducting security analysis and performance analysis, EMAP is in contestable to be secure and economical